Development of SETS-based modules for understanding zoological concepts on Lemukutan Island - Tesa Manisa; Mustika Sari (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Zoology, as a branch of biology, not only focuses on theoretical aspects but also requires mastery of practical skills in observing, analyzing, and understanding the interactions between organisms and their environment. Observations during the field study on Lemukutan Island revealed that many students were still confused about identifying the names of species and body parts of invertebrate animals encountered during the field exploration. This study aims to determine the validity, student responses, and effectiveness of the SETS-based teaching module through invertebrate exploration on Lemukutan Island. This research is an R&D study using the ADDIE model. The data collection tools used in this study included validation sheets, student response questionnaires, and zoology concept understanding tests. Data analysis involved calculating validation scores, student questionnaires, and N-gain score results from the zoology concept understanding test. The results showed that the SETS-based module is valid, practical, and effective for enhancing students' conceptual understanding of zoology. It received an average validity score of 1.00, a student response percentage of 79%, and an N-gain score of 0.783 (high category). These findings suggest that the module is suitable for integration into the invertebrate systematics curriculum and can improve the relevance and engagement of learning by linking zoological content to local biodiversity contexts such as those on Lemukutan Island.Abstrak. Zoologi sebagai salah satu cabang ilmu biologi tidak hanya menitikberatkan pada aspek teoritis saja, tetapi juga menuntut penguasaan keterampilan praktis dalam mengamati, menganalisis, dan memahami interaksi antara organisme dengan lingkungannya. Hasil observasi pada saat kuliah lapangan di Pulau Lemukutan menunjukkan bahwa banyak mahasiswa yang masih bingung ketika menyebutkan nama-nama spesies dan bagian tubuh hewan invertebrata yang ditemukan pada saat eksplorasi lapangan. Penelitian ini bertujuan untuk mengetahui validitas, respon mahasiswa, dan efektivitas modul ajar berbasis SETS melalui eksplorasi invertebrata di Pulau Lemukutan. Penelitian ini merupakan jenis penelitian R&D dengan menggunakan desain ADDIE. Alat pengumpul data yang digunakan dalam penelitian ini adalah lembar validasi, angket respon mahasiswa, dan tes pemahaman konsep zoologi. Analisis data menggunakan perhitungan skor validasi, angket mahasiswa, dan skor hasil N-gain tes pemahaman konsep Zoologi mahasiswa. Hasil penelitian menunjukkan bahwa modul berbasis SETS valid, praktis, dan efektif dalam meningkatkan pemahaman konsep zoologi mahasiswa. Modul ini memperoleh skor validitas rata-rata sebesar 1,00, persentase respons mahasiswa sebesar 79%, dan skor N-gain sebesar 0,783 (kategori tinggi). Temuan ini menunjukkan bahwa modul layak diintegrasikan ke dalam kurikulum sistematika invertebrata dan dapat meningkatkan relevansi serta keterlibatan pembelajaran dengan mengaitkan konten zoologi pada konteks keanekaragaman hayati lokal seperti di Pulau Lemukutan.